Closure operators in the categories of modules. Part II (Hereditary and cohereditary operators) - Kashu, A.I. (Algebra and Discrete Mathematics, 2013)
This work is a continuation of the paper [1] (Part I), in which the weakly hereditary and idempotent closure operators of the category R-Mod are described. Using the results of [1], in this part the other classes of closure operators C are characterized by the associated functions F₁с and F₂с which separate in every module M ∈ R-Mod the sets of C-dense submodules and C-closed submodules. This method is applied to the classes of hereditary, maximal, minimal and cohereditary closure operators.